Analysis of Potentials and Challenges of Culture-based Learning in Indonesia : A Systematic Literature Review - Dimas Febriansyah Krisna Dwiputra; Dadang Sundawa (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to identify the potential and challenges of culture-based learning in Indonesia. This study used the systematic literature review method with the PRISMA 2020 model. Data were collected from Harzing's Publish or Perish whose database comes from Scopus and Google Scholar. The data search used three keywords including "culture-based education", “culture-based learning”, "pembelajaran berbasis budaya", and "Pendidikan berbasis budaya". A total of 1,727 article data were obtained but only 25 articles met the inclusion criteria for the analysis stage. Then, data were analyzed using thematic analysis techniques. The results of the study showed that culture-based learning has the potential to be applied to create quality human resources in Indonesia. This culture-based learning not only provides benefits in the aspects of knowledge, attitudes, and academic behavior but also strengthens the existence of local culture and even internalizes the values contained to develop the noble character of the students. Besides, the main challenge of culture-based learning in Indonesia was the teacher's understanding and skills in integrating local culture with the learning process and how to package the learning to fits the characteristics of students as the digital native generation who are close to the development of digital technology.